Java & XML - McLaughlin, Brett (O'Reilly, 2007)
Java and XML, 3rd Edition, shows you how to cut through all the hype about XML and put it to work. It teaches you how to use the APIs, tools, and tricks of XML to build real-world applications. The result is a new approach to managing information that touches everything from configuration files to web sites. After two chapters on XML basics, including XPath, XSL, DTDs, and XML Schema, the rest of the book focuses on using XML from your Java applications. This third edition of Java and XML covers all major Java XML processing libraries, including full coverage of the SAX, DOM, StAX, JDOM, and.